2015
DOI: 10.1002/elan.201500351
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Total PSA Using Magnetic Beads and a Re‐usable Screen Printed Carbon Electrode Array

Abstract: [a] 1IntroductionProstate cancer accounts for 10 %o fa ll deaths from cancer [1,2] and the prostate specific antigen (PSA) is the best serumm arkerc urrently available for the preoperative diagnosis and screening for this cancer. PSA in serum circulates under two forms (free PSA(fPSA) [3] and complexed,b eing the predominanto ne the complex with a 1-antichymotripsin (PSA-ACT) [4].I np rostate cancer diagnosis,t he sum of both forms noted total PSA (tPSA) is used to determine somec ut off.Avalue of tPSA abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Lately, a lot of immunoassay methods related to PSA detection have been reported including enzyme‐linked immunosorbent‐assays (ELISA) , electrochemical immunoassays , chemiluminescent immunoassays and bioluminescent immunoassay . Although those methods are reliable, most of them require long measurement procedures, high costs, complex equipment, highly qualified personnel and are not appropriate for massive decentralized assays.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Lately, a lot of immunoassay methods related to PSA detection have been reported including enzyme‐linked immunosorbent‐assays (ELISA) , electrochemical immunoassays , chemiluminescent immunoassays and bioluminescent immunoassay . Although those methods are reliable, most of them require long measurement procedures, high costs, complex equipment, highly qualified personnel and are not appropriate for massive decentralized assays.…”
Section: Introductionsupporting
confidence: 84%
“…Table displays the electroanalytical characteristics of recent reported electrochemical immunosensor for PSA detection and those of the developed immunosensor. As it can be seen, the proposed immunosensor improves the width of the concentration range and the LOD in comparison with some of the recent reported sensors . Although other immunosensors show lower LOD that the achieved in this work (Table ), it has to be considered that the construction of these biosensors involves more complex schemes and higher costs (since more materials, reagents and/or steps are needed).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other immunosensors reported by analytical studies (Table ), the developed immunosensor showed better analytical performance in view of the linear range and the limit of detection. Such excellent sensing performance can be attributed following factors of (a) excellent conductivity and unique structural features Fe 3 O 4 , (b) large active surface area of Fe 3 O 4 modified electrode provides high density and a favorable microenvironment for oriented antibody immobilization retaining the biological activity, and (c) to further enhance the electrochemical signal, CysA‐AuNPs/TB labeled HRP‐Ab2 was used as a tracer for good catalytic reduction of [Fe (CN) 6 ] 3‐/4‐ .…”
Section: Resultsmentioning
confidence: 82%
“…Compared with other immunosensors reported by analytical studies (Table 1), [24][25][26][27][28][29]31 the developed immunosensor showed better analytical performance in view of the linear range and the limit of As shown in Figure S5, the current signal of the proposed immunosensor was compared with the current signal obtained in threefold excess of different interfering species. There are no significant changes in the signals observed, and the interference was nearly negligible, suggesting the acceptable selectivity of the fabricated immunosensor for the determination of PSA.…”
Section: Analytical Approachmentioning
confidence: 95%
“…Biscay et al. investigated a screening device using magnetic beads as solid phase to develop an immunoassay for the detection of total PSA (tPSA) in serum. Here, the tPSA detection was performed by using superparamagnetic beads (1 mm) modified with streptavidin and an 8‐channel screen printed electrode array.…”
Section: Magnetic Immunoassaysmentioning
confidence: 99%